Contrasting Trends of Population Size Change for Two Eurasian Owlet Species—Athene brama and Glaucidium radiatum From South Asia Over the Late Quaternary - Natesh, Meghana; Vinay, K. L.; Ghosh, Samriddha; Jayapal, Rajah; Mukherjee, Shomita; Vijay, Nagarjun; Robin, V. V. (Frontiers in Ecology and Evolution, 2020)
Climatic oscillations over the Quaternary have had a lasting impact on species’ distribution, evolutionary history, and genetic composition. Many species show dramatic population size changes coinciding with the last glacial period. However, the extent and direction of change vary across biogeographic regions, species-habitat associations, and species traits. Here we use genomic data to assess population size changes over the late Quaternary using the Pairwise Sequential Markovian Coalescent (PSMC) approach in two Eurasian Owlet species – the Spotted Owlet, Athene brama, and the Jungle Owlet, Glaucidium radiatum. While Spotted Owlets are typically associated with open habitats, Jungle Owlets are found in deciduous forests and scrublands. We find that the effective population size for the Spotted Owlet increased after the Interglacial period till the Last Glacial Maxima and subsequently declined towards the Mid-Holocene. On the other hand, effective population size estimates for the Jungle Owlet increased gradually throughout this period. These observations are in line with climatic niche model-based predictions for range size change for both species from a previous study and suggest that habitat associations at the local scale are important in determining responses to past climatic and vegetational changes. The Spotted Owlet result also aligns well with the expectation of open habitat expansion during the arid Glacial Maxima, whereas for the Jungle Owlet the contrasting expectation does not hold. Therefore, assessing the impacts of glacial history on population trajectories of multiple species with different habitat associations is necessary to understand the impacts of past climate on South Asian taxa.